The use of indirect methods for the prediction of lucerne quality in the first cut under the conditions of Central Europe - J. Hakl; J. Šantrůček; P. Fuksa; L. Krajíc (Czech Journal of Animal Science, 2010)
The goal of this study was to compare the growing degree-days (GDD) and predictive equations for alfalfa quality (PEAQ) for the prediction of lucerne quality and to test their accuracy and suitability in the first cut period in Central Bohemia. Several additional stand parameters were verified in order to increase the accuracy of the quality estimate under these environmental conditions. In 2004-2007, the measurement and sampling were repeatedly realized from the late vegetative to the early bloom stage in six replications. For the GDD model across the years, the obtained R2 for NDF, ADF and CP were 0.40, 0.57 and 0.65, respectively. It seems that the forage quality response to accumulated GDD was related to the stand development and it could be the reason for low R2 across all the years. For the PEAQ model, R2 were 0.62, 0.92, and 0.85, respectively. Similarly like in the GDD model, the effect of stand development across the years on changes in the slopes of equations was observed. The accuracy of the model combination was not higher in comparison with the PEAQ model. The count of stems per plant, density of stems per m2, dry matter yield and average stem weight improved the NDF content prediction within a four-year period. In these models, variables which represent the stand development should be taken into account.